2019
DOI: 10.3389/fonc.2019.01029
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and mRNA Interaction Network Regulates the Malignant Transformation of Human Bronchial Epithelial Cells Induced by Cigarette Smoke

Abstract: This study analyzes the correlation and interaction of miRNAs and mRNAs and their biological function in the malignant transformation of BEAS-2B cells induced by cigarette smoke (CS). Normal human bronchial epithelial cells (BEAS-2B) were continuously exposed to CS for 30 passages (S30) to establish an in vitro cell model of malignant transformation. The transformed cells were validated by scratch wound healing assay, transwell migration assay, colony formation and tumorigenicity assay. The miRNA and mRNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
“…However limited studies have demonstrated the role of miR-195-5p in lung cancer. It is reported that miR-195-5p had lower expression in lung cancer and may act as a biomarker that contributed to the diagnosis of lung cancer and the detection of its high-risk population [28,29]. Moreover, miR-195-5p functions as a predictor of poor prognosis by directly targeting CIAPIN1 [30].…”
Section: Ivyspringmentioning
confidence: 99%
“…Additionally, low CH25H levels in leukocytes from melanoma patients were correlated with poor prognosis (Ortiz et al, 2019 ). CORO2B was found to be involved in many biological processes of malignant transformation in BEAS-2B cells induced by cigarette smoke (Wang et al, 2019 ). LOC51089, also called C1QA, was found to be involved in the innate immune system and was associated with the expression of PD-L1 (Olkhov-Mitsel et al, 2020 ), and its abnormal expression in tumor tissues was confirmed in head and neck squamous cell carcinoma and clear cell renal cell carcinoma (Yu et al, 2019 ; Apanovich et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1.5 g RNA per sample was used as input material for the RNA library construction. The mRNA sequencing procedure has been described in detail in our previous article, and the raw data has been deposited in the Sequence Read Archive (SRA) database ( https://trace.ncbi.nlm.nih.gov/Traces/sra/ ) with identifier SRP181756 [ 43 ]. Genes were computed by summing the fragments per kilo-base of exon per million fragments mapped (FPKM) of transcripts in each gene group.…”
Section: Methodsmentioning
confidence: 99%